A genome-wide association study identifies genomic regions for virulence in the non-model organism Heterobasidion annosum s.s. - Kerstin Dalman; Kajsa Himmelstrand; Åke Olson; Mårten Lind; Mikael Brandström-Durling; Jan Stenlid (PLoS ONE, 2013)
The dense single nucleotide polymorphisms (SNP) panels needed for genome wide association (GWA) studies have hitherto been expensive to establish and use on non-model organisms. To overcome this, we used a next generation sequencing approach to both establish SNPs and to determine genotypes. We conducted a GWA study on a fungal species, analysing the virulence of Heterobasidion annosum s.s., a necrotrophic pathogen, on its hosts Picea abies and Pinus sylvestris. From a set of 33,018 single nucleotide polymorphisms (SNP) in 23 haploid isolates, twelve SNP markers distributed on seven contigs were associated with virulence (P<0.0001). Four of the contigs harbour known virulence genes from other fungal pathogens and the remaining three harbour novel candidate genes. Two contigs link closely to virulence regions recognized previously by QTL mapping in the congeneric hybrid H. irregulare × H. occidentale. Our study demonstrates the efficiency of GWA studies for dissecting important complex traits of small populations of non-model haploid organisms with small genomes.